Formal compensation practices in family SMEs. Issue 1 (20th February 2017) - Michiels, Anneleen
Abstract : Purpose: By investigating the use of formal compensation practices in family small- and medium-sized enterprises (SMEs), the purpose of this paper is to provide important new insights in these issues for academics, as well as family business practitioners, prospective applicants and financiers of family businesses. Moreover, this study includes a contingency that allows to explore heterogeneity across family businesses in their use of formal compensation practices: the CEO type. Design/methodology/approach: A survey of 124 small- and medium-sized Belgian family businesses to explore the use of formal compensation practices is analyzed by the author. Findings: The results support the hypothesis that family firms with a family CEO adopt significantly less formal compensation practices than their counterparts that are led by a non-family CEO. Research limitations/implications: Generalizing the findings of this study must be taken with care, as the findings are based on a cross-sectional sample of family SMEs in one country, Belgium. Future research can build on these findings with studies on larger samples in other countries. Practical implications: This study may be interesting for family business practitioners and consultants, as it provides insight in the actual use of formal compensation practices that are recommended as a best practice in numerous practitioner handbooks. Also, the results of this study might be important for prospective applicants and financiers, since the compensation system is an important communication device to signal legitimacy to external stakeholders. Originality/value: Compensation issues are among the main challenges SMEs, especially family firms, face. Despite the clear importance of this matter, academic interest has been rather limited. This paper therefore displays sound descriptive survey results and empirically investigates the determinants of the use of formal compensation practices in Belgian family SMEs by distinguishing between different types of family businesses.